Hydroxysafflor Yellow A Alleviates Ovalbumin-Induced Asthma in a Guinea Pig Model by Attenuateing the Expression of Inflammatory Cytokines and Signal Transduction - Zheng, Meng; Guo, Xinjing; Pan, Ruiyan; Gao, Jianwei; Zang, Baoxia; Jin, Ming (Frontiers in Pharmacology, 2019)
Hydroxysafflor yellow A (HSYA) is an effective ingredient of the Chinese herb Carthamus tinctorius L. In this study, we aimed to evaluate the effects of HSYA on ovalbumin (OVA)-induced asthma in guinea pigs, and to elucidate the underlying mechanisms. We established a guinea pig asthma model by intraperitoneal injection and atomized administration OVA. Guinea pigs were injected intraperitoneally with HSYA (50, 75, 112.5 mg/kg) once daily from days 2 to 22 before OVA administration. We examined biomarkers including lung function, pulmonary histopathology, immunoglobulin E (IgE), Th1/Th2 relative inflammatory mediators, and related pathways. Pathological changes in lung tissues were detected by hematoxylin and eosin and periodic acid-Schiff staining. Phosphorylation levels of JNK mitogen-activated protein kinase (MAPK), p38 MAPK, ERK MAPK, and inhibitor of nuclear factor κBα (IκBα) were detected by western blot. plasma levels of total IgE, platelet-activating factor (PAF), and interleukin (IL)-3 were detected by enzyme-linked immunosorbent assay (ELISA). Expression levels of tumor necrosis factor (TNF)-α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-13, and interferon (IFN)-γ were detected by ELISA and real-time quantitative polymerase chain reaction. HSYA significantly reduced airway resistance, improved dynamic lung compliance, and attenuated the pathologic changes. HSYA also inhibited the phosphorylation of JNK MAPK, p38 MAPK, ERK MAPK, and IκBα, and inhibited the OVA-induced elevations of IgE, PAF, IL-1β, IL-6, IL-4, IL-5, and IL-13 and the decreases in TNF-α, IFN-γ, IL-2, and IL-3. These findings suggest that HSYA has a protective effect on OVA-induced asthma through inhibiting the Th1/Th2 cell imbalance and inhibiting activation of the MAPK signaling pathway